Sistem Kontrol Pesawat Tanpa Awak Untuk Menentukan Waypoint Berbasis Ardupilot - Putri Rachmawati; Muhammad Haydar Asyam (Quantum Teknika : Jurnal Teknik Mesin Terapan, 2021)
An unmanned Aerial Vehicle (UAV) is a type of unmanned aerial vehicle which is controlled by a remote system. This type of aircraft is usually controlled by remote control from outside the plane and can also move automatically based on a program that has been programmed on the computer system. In this study, a control system with autopilot and remote control is used. This study aims to apply the ardupilot system to the super heavy model aircraft with a long-range flight mode control system using the Futaba T8J (8 channel) radio control. The results of this study took a flight time of 15.02 minutes with an altitude of 30 meters, a waypoint radius of 20 meters with a speed of 10 m / s.